2022
DOI: 10.46483/deuhfed.1010957
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Fatigue and Risk Factors in Nurses in The Covid-19 Pandemic

Abstract: Giriş: Hemşirelik mesleğinin doğası gereği hemşireler merhamet yorgunluğu yaşayabilir. Pandemi dönemi bu riski artırabilir ve bu durum hemşireyi, hastayı ve sağlık sistemini olumsuz etkileyebilir. Amaç: Bu çalışmanın amacı pandemi sürecinde hemşirelerin yaşadığı merhamet yorgunluğunu değerlendirmektir. Yöntem: Kesitsel tipteki bu araştırma, Eskişehir’deki bir hastanede çalışan 280 hemşire ile gerçekleştirildi. Ölçüm aracı olarak yapılandırılmış soru formu ve Merhamet Yorgunluğu-Kısa Ölçeği kullanı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…54 Also, the findings were similar to those of a Turkish study that reported a substantial difference in anxiety levels between nurses and family members with COVID-19. 55 Despite the study's significant findings, a few limitations should be considered. The study is cross-sectional, therefore it does not account for the direct impact of stress on resilience.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…54 Also, the findings were similar to those of a Turkish study that reported a substantial difference in anxiety levels between nurses and family members with COVID-19. 55 Despite the study's significant findings, a few limitations should be considered. The study is cross-sectional, therefore it does not account for the direct impact of stress on resilience.…”
Section: Discussionmentioning
confidence: 97%
“…54 Also, the findings were similar to those of a Turkish study that reported a substantial difference in anxiety levels between nurses and family members with COVID-19. 55…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are at the forefront of this process. Depending on the situation, nurses provide compassionate care, experience patients’ pain and trauma, and empathize with them; this can lead to compassion fatigue (CF) ( Uslu, 2020 ). As a result of compassion fatigue, nurses experience symptoms of physical, emotional or spiritual, and social exhaustion ( Şirin & Yurttaş, 2015 ).…”
Section: Introductionmentioning
confidence: 99%